Breaking barriers in Boerhaave syndrome: a case of successful non-surgical treatment - M., Shivadev; Gupta, Brajesh B.; Chandak, Unmed; Bansod, Prasad; Gupta, Shweta; Mehta, Neel; Tolani, Shikha; Behera, Subodh; Akulwar, Sanskruti; Nighot, Gaurav; Ganorkar, Ashlesha; Sawadetkar, Nishant (International Surgery Journal, 2025)
Boerhaave syndrome is a rare and life-threatening condition characterized by spontaneous esophageal rupture, commonly resulting from severe vomiting. It carries a high mortality rate if untreated, particularly in delayed presentations. This report details a 44-year-old male with symptoms of breathlessness, chest pain, and vomiting after binge drinking. Initial management included nasogastric and intercostal drainage, antibiotics, and total parenteral nutrition. Diagnostic imaging revealed a left-sided esophageal tear with a fistula to the pleural cavity. Conservative treatment combined endoluminal vacuum therapy with other supportive measures, successfully reducing the esophageal defect and associated complications. The patient recovered without requiring additional surgical intervention, highlighting the potential of conservative approaches in carefully selected cases of Boerhaave syndrome. This case underscores the importance of timely diagnosis, multidisciplinary management, and advanced endoscopic therapies in achieving positive outcomes for a condition traditionally managed surgically.